Sosialisasi Standar Kota Layak Anak dan Model Hunian Ramah Lingkungan di Pulau Tidung, Kepulauan Seribu Kotamadya Jakarta Utara, Provinsi DKI Jakarta - Uras Siahaan; Susanti Muvana Nainggolan; Stepanus Andi Saputra; Charles OP Marpaung; Louisa Ariantje Langi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Tidung Island is part of the Thousand Islands, which is generally known for its tourism potential, attracting many visitors both from within the country and abroad. Visitors has an experience satisfaction and also wish to return to Tidung Island. This makes it essential for Tidung Island to nurture the growth of its children as the future generation, ensuring that the implementation of the 5 clusters of the “Kota Layak Anak” is implemented for the proper growth and development of children on Tidung Island. Based on discussions with the local government team and literature studies, the third of the “Kota Layak Anak” has become the main focus to be implemented through this activity. In this case, the right of children to receive basic health and welfare will be achieved by conducting socialization on the prevention and handling of stunting in children, as well as promoting eco-friendly housing on Tidung Islan.